Model for assessment front crawl sprint swimming potential at youth water polo players: International standardisation approach - Dopsaj, M.; Perazzetti, A.; Özkol, M. Z.; Ošljak, A.; Novoselac, N.; Tessitore, A. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION: Beside the technical and tactical skills, the most swimming or physical activities in water polo last for <20 seconds, with mostly very intense movements, where swimming sprints averaging between 7 to 14 seconds, mostly by the use of crawl stroke1. The purpose of the study was to define model for assessment potential for front crawl sprint swimming at youth water polo players through an international standardisation approach.